Letting Go of Grades: Creating an Environment of Autonomy and a Focus on Learning for High Achieving Students (Teaching and Learning Inquiry, 2022)
In this essay we discuss an iterative, reflective writing assignment (the “learning charter”) as a way to understand how high-achieving students experienced an ungrading learning environment. Working with evidence from student written reflection and in-class conversations, we chronicle how students articulated their perspectives on this approach through the fifteen-week semester. Our findings indicate that despite initial uncertainty, students found the environment to be one that promoted learning for the sake of learning, cultivated mental wellness, and compelled them to pursue meaningful questions about their own educational goals and experience. While this development was not without feelings of conflict and struggle throughout the course, by the end of it, students reported a renewed focus on the value of learning. We suggest that the strategies employed in this course might be successfully adopted in or adapted to other courses for high-achieving students, as well as other student populations.